Signature pieces: on the institution of authorship - Kamuf, Peggy (Cornell University Press, 1988)
Some contemporary approaches to literature still accept the separation of historical, biographical, external concerns from formal, internal ones. On the borderline that lends this division between inside and outside its apparent coherence is signature. In Peggy Kamuf’s view, studying signature will help us to rediscover some of the stakes of literary writing beyond the historicist/formalist opposition. Drawing on Derrida’s extensive work on signatures and proper names, Kamuf investigates authorial signature in key writers from Rousseau to Woolf, as well as the implications of signature for the institutions of authorship and criticism